Reflections on six decades of professional social work fundamental principles for social workers - Lawson, Thomas R. (Párbeszéd: Szociális munka folyóirat, 2021)
What principles have I found to exist over my six decades of social work that are central to the profession and are still applicable in today’s complex world? What has guided social work in its quest to address the myriad, ever changing and most difficult problems facing our societies irrespective of the continent or country? In my professional journey these practice guides can be synthesized into 13 basic principles that can serve as a strong foundation and are still highly useful today. In my over 55 years as a professional social worker, studying the individuals and writers who were seminal to the profession to those who emerged during the mid-20th century, certain principles emerged. These principles arose from both practice and academic areas and have provided grounding and guidance that has led to the successful delivery of social work irrespective of the decade or location.